The stoichiometry of soil microbial biomass determines metabolic quotient of nitrogen mineralization - Zhaolei Li; Zhaoqi Zeng; Dashuan Tian; Jinsong Wang; Zheng Fu; Bingxue Wang; Ze Tang; Weinan Chen; Han Y H Chen; Changhui Wang; Chuixiang Yi; Shuli Niu (Environmental Research Letters, 2020)
Soil nitrogen (N) mineralization is crucial for the sustainability of available soil N and hence ecosystem productivity and functioning. Metabolic quotient of N mineralization ( Q _min ), which is defined as net soil N mineralization per unit of soil microbial biomass N, reflects the efficiency of soil N mineralization. However, it is far from clear how soil Q _min changes and what are the controlling factors at the global scale. We compiled 871 observations of soil Q _min from 79 published articles across terrestrial ecosystems (croplands, forests, grasslands, and wetlands) to elucidate the global variation of soil Q _min and its predictors. Soil Q _min decreased from the equator to two poles, which was significant in the North Hemisphere. Soil Q _min correlated negatively with soil pH, total soil N, the ratio of soil carbon (C) to N, and soil microbial biomass C, and positively with mean annual temperature and C:N ratio of soil microbial biomass at a global scale. Soil microbial biomass, climate, and soil physical and chemical properties in combination accounted for 41% of the total variations of global soil Q _min . Among those predictors, C:N ratio of soil microbial biomass was the most important factor contributing to the variations of soil Q _min (the standardized coefficient = 0.39) within or across ecosystem types. This study emphasizes the critical role of microbial stoichiometry in soil N cycling, and suggests the necessity of incorporating soil Q _min into Earth system models to better predict N cycling under environmental change.